Comparative phylogeographies of six species of hinged terrapins (Pelusios spp.) reveal discordant patterns and unexpected differentiation in the P. castaneus/P. chapini complex and P. rhodesianus. (25th September 2015) - Kindler, Carolin; Moosig, Maggie; Branch, William R.; Harvey, James; Kehlmaier, Christian; Nagy, Zoltán T.; Prokop, Hynek; Široký, Pavel; Fritz, Uwe
Abstract : Using up to 2117 bp of mitochondrial DNA and up to 2012 bp of nuclear DNA, we analysed phylogeographic differentiation of six widely distributed species of African hinged terrapins ( Pelusios spp.) representing different habitat types. Two taxa each live in savannahs or in forests and mesic savannahs, respectively, and the remaining two species occur in intermediate habitats. The species living in forests and mesic savannahs do not enter dry savannahs, whereas the savannah species may occur in dry and wet savannahs and even in semi‐arid steppe regions. We found no obvious correlation between habitat type and phylogeographic pattern: one savannah species ( P. rhodesianus ) shows phylogeographic structure, i.e. pronounced genetic differences among geographically distinct populations, and the other ( P. nanus ) not. One species inhabiting forests and mesic savannahs ( P. carinatus ) has phylogeographic structure, the other ( P. gabonensis ) not. The same pattern is true for the two ecologically intermediate species, with phylogeographic structure present in P. castaneus and absent in P. chapini . Nuclear evidence suggests that the latter two taxa with abutting and partially overlapping ranges are distinct, while mtDNA is only weakly differentiated. Pelusios castaneus shows pronounced phylogeographic structure, which could reflect Pleistocene range interruptions correlated with the fluctuating forest cover in West and Central Africa. Our results do not support the recognition of an extinct subspecies of P. castaneus for the Seychelles. Pelusios carinatus contains two well supported clades, which are separated by the Congo River. This species is closely related to P. rhodesianus, a taxon consisting of two deeply divergent mitochondrial clades. One of these clades is paraphyletic with respect to P. carinatus, but the two clades of P. rhodesianus are not differentiated in the studied nuclear markers and, again, paraphyletic with respect to P. carinatus . Using mtDNA sequences from the type material of P. rhodesianus, we were able to allocate this name to one of the two clades. However, owing to the confusing relationships of P. rhodesianus and P. carinatus, we refrain from taxonomic decisions.